(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article presents a systematic analysis of current scientific and methodological problems in teaching physics to future engineers at technical universities. Traditional reproductive and problem-based teaching methods are comparatively studied, and their role in the formation of engineering competencies is substantiated. Key problems are identified, such as the outdated material and technical base of laboratory classes, insufficient level of interdisciplinary integration, and the lack of systematic use of digital technologies (PhET, MATLAB, LabVIEW, etc.). Within the framework of Resolution No. PQ-5032 of the President of the Republic of Uzbekistan, practical recommendations have been developed for improving the methodology of teaching physics. The results of the article can serve as a methodological guide for the physics departments of technical universities.